2013
DOI: 10.3762/bjnano.4.42
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic behaviour of Fe-doped ZnO nanograined films

Abstract: SummaryThe influence of the grain boundary (GB) specific area s GB on the appearance of ferromagnetism in Fe-doped ZnO has been analysed. A review of numerous research contributions from the literature on the origin of the ferromagnetic behaviour of Fe-doped ZnO is given. An empirical correlation has been found that the value of the specific grain boundary area s GB is the main factor controlling such behaviour. The Fe-doped ZnO becomes ferromagnetic only if it contains enough GBs, i.e., if s GB is higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 74 publications
4
45
0
1
Order By: Relevance
“…As it is clear from the above morphology and PL results that sp-d exchange interactions and presence of defects are increased with increasing Fe concentration, which may be responsible for the origin of observed FM in Fe doped ZnO nanostructures. Moreover, it has been reported that grain boundaries and grain sizes also play a significant role in the ferromagnetic properties of TM doped ZnO [35]. The ferromagnetic behavior of Fe doped ZnO is believed to be more prominent, if it is comprised of nano-grains [36].…”
Section: Photoluminescence and Ferromagnetic Propertiesmentioning
confidence: 99%
“…As it is clear from the above morphology and PL results that sp-d exchange interactions and presence of defects are increased with increasing Fe concentration, which may be responsible for the origin of observed FM in Fe doped ZnO nanostructures. Moreover, it has been reported that grain boundaries and grain sizes also play a significant role in the ferromagnetic properties of TM doped ZnO [35]. The ferromagnetic behavior of Fe doped ZnO is believed to be more prominent, if it is comprised of nano-grains [36].…”
Section: Photoluminescence and Ferromagnetic Propertiesmentioning
confidence: 99%
“…Hence the magnetic order in our samples could be ferromagnetic regions due to Fe 3+ -F-center-Fe 3+ pairs and paramagnetic sites due to isolated F-centers. Further amorphous grain boundaries may also contribute to the observed ferromagnetism as seen in TM-doped ZnO [40,41] and In 2 O 3 [42] thin films, as our grains are around 100 nm. It was found that polycrystalline samples with high specific area of grain boundaries, i.e.…”
Section: Resultsmentioning
confidence: 87%
“…This is due to the influence of the addition of the surfactant S. rarak on the growth of ZnO nanoparticles. Although the exact non-trivial behavior of ZnO nanocrystals could not be described, the properties may be driven by the grain boundaries in studied samples [12]. On the other hand, the SEM analysis also confirms that ZnO nanoparticles have different morphologies by varying the concentration of the medium.…”
Section: S Rarak 0%mentioning
confidence: 77%